From flexing to community engagement and repurchase intention: An Indonesian Muslimah luxury brand approach - Haque, Marissa Grace; Rimadias, Santi; Ernaningsih, Indria (Jurnal Manajemen dan Pemasaran Jasa, 2023)
Starting from the flexing phenomenon, transforming into an exclusive group emotional bond, ending with the intention to buy back Indonesian luxury fashion products, used as a marketing approach for "Buttonscarves." It is broken down into utilitarian values, hedonic values, and brand community engagement on customer satisfaction, the implications for repurchase intention, then tested and analyzed for each roles. A muslimah community created with an appropriate use called "BS Lady." 61 members joined the survey, fill-in the a 1-6 scale structured online questionnaire, analyzed with PLS-SEM through SmartPLS 3.0 software. Research conducted in March 2023. Results show that brand community engagement and customer satisfaction have proven to have a positive effect on repurchase intention. Utilitarian value is proven to have a positive effect on customer satisfaction. Indirectly, hedonic values affect repurchase intention through customer satisfaction. Finally, it was found that utilitarian values and hedonic values have no on repurchase intention. Keywords: brand community engagement; customer satisfaction; hedonic values; repurchase intention; utilitarian value